2014
DOI: 10.3390/molecules190812320
|View full text |Cite
|
Sign up to set email alerts
|

Rumphellaones B and C, New 4,5-Seco-Caryophyllane Sesquiterpenoids from Rumphella

Abstract: Two new 4,5-seco-caryophyllane sesquiterpenoids, rumphellaones B (1) and C (2), which were found to possess unprecedented γ-lactone moieties, were obtained from the OPEN ACCESSMolecules 2014, 19 12321 gorgonian coral Rumphella antipathies. The structures of 1 and 2 were elucidated by spectroscopic methods and compound 2 was found to display modest inhibitory effects on the generation of superoxide anions and the release of elastase by human neutrophils at a concentration of 10 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
(15 reference statements)
1
15
0
2
Order By: Relevance
“…695 The study also reported an extensive number of cometabolites 1080-1083 that had been previously reported from terrestrial plants or as semi-synthetic derivatives 1084-1090. Other sesquiterpenes 1091-1110 have been reported from Rumphella antipathies, [696][697][698] Lemnalia philippinensis, 699 Menella kanisa, 700 Nephthea erecta, 701 an unidentied gorgonian, 702 Dendronephthya sp., 703 Sinularia kavarattiensis, 704 Echinogorgia sassapo reticulata 705 and Anthrogorgia ochracea. 706 Of these sesquiterpenes, rumphellaoic acid A 1093 697 contains a unique skeleton, while shagenes A 1102 and B 1103 702 and ochracenoid A 1109 706 contain rarely reported skeletons.…”
Section: Cnidariansmentioning
confidence: 99%
“…695 The study also reported an extensive number of cometabolites 1080-1083 that had been previously reported from terrestrial plants or as semi-synthetic derivatives 1084-1090. Other sesquiterpenes 1091-1110 have been reported from Rumphella antipathies, [696][697][698] Lemnalia philippinensis, 699 Menella kanisa, 700 Nephthea erecta, 701 an unidentied gorgonian, 702 Dendronephthya sp., 703 Sinularia kavarattiensis, 704 Echinogorgia sassapo reticulata 705 and Anthrogorgia ochracea. 706 Of these sesquiterpenes, rumphellaoic acid A 1093 697 contains a unique skeleton, while shagenes A 1102 and B 1103 702 and ochracenoid A 1109 706 contain rarely reported skeletons.…”
Section: Cnidariansmentioning
confidence: 99%
“…Sesquiterpenoid analogs, particularly caryophyllane- and clovane-type analogs, are major constituents of the extracts of gorgonian coral Rumphella antipathies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Our continuing studies on the chemical constituents of R. antipathies (family Gorgoniidae) ( Chart 1 ), collected off the waters of Taiwan, have led to the isolation of a novel sesquiterpenoid, rumphellaoic acid A ( 1 ) ( Chart 1 and Supplementary Figures S1–S7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rumphellaone A ( 1 ) is a 4,5- seco -caryophyllane sesquiterpenoid possessing an unprecedented γ-lactone moiety that shows citotoxicity against human T-cell acute lymphoblastic leukemia tumor cells (IC 50 = 12.6 μg/mL). 1 This sesquiterpenoid was isolated from Rumphella antipathies , a gorgonian coral that has produced several other caryophyllane and clovane sesquiterpenes ( Figure 1 ). 2 Isolation of 402 g of wet R. antipathies yielded only 0.9 mg of 1 .…”
mentioning
confidence: 99%